PROJECT INVESTMENT ANALYSIS OF ZULU OIL FIELD DEVELOPMENT IN CENTRAL SUMATRA USING COST RECOVERY AND GROSS SPLIT PRODUCTION SHARING CONTRACTS - Respati / 29115273, Haris
Zulu field is an oil field with high unrecovered oil reserves in Central Sumatera. Zulu field oil currently produced 4% of its reserve potential, and Zulu PSC contract will end in 4 years. Objective of the project is to assess the economic profitability of the unrecovered oil field and compare using PSCÃ‚Â’s Cost Recovery and Gross Split terms. This project will use NPV, IRR, PBP and DPI as the profitability indicatorsThe highest DPI will be the best choice from contractor point of view. On the other hand, government will choose the best alternative based on high NPV, peak production and reserve. The sensitivity analysis shows that the estimation of the oil production is the most influential factor on the project's economic value. Investment costs include capital cost (CAPEX) and operating costs (OPEX). Capital expenditure (CAPEX) covers the cost of making road access to wells, drilling costs and piping costs. Capital expenditure divided into tangible and intangible cost, declining balance depreciation will apply to tangible cost. Operating costs (OPEX) include the cost of oil treatment from the subsurface, the cost of processing fluids and transport to the final sales. From Government of Indonesia point of view, they would also prefer Maximum Recovery strategy compared other alternatives. Maximum Recovery strategy has biggest NPV, reserve and peak production. Government of Indonesia main concern is about how big the project is, so it would be having high impact on government revenue, in this case is tax. Government of Indonesia also prefers high production and reserves, as this has significant economic and political impacts. High production will create more money for the government and will politically strengthen their performance achievements. Sensitivity analysis shows that reserve estimation is the most influencing factor for project economic. This can be seen on the simulation of sensitivity between reserve with NPV, IRR and DPI. As a result, the project team should pay more special attention to reserve estimation.